2017
DOI: 10.1136/annrheumdis-2017-211544
|View full text |Cite
|
Sign up to set email alerts
|

TNF blockers inhibit spinal radiographic progression in ankylosing spondylitis by reducing disease activity: results from the Swiss Clinical Quality Management cohort

Abstract: ObjectivesTo analyse the impact of tumour necrosis factor inhibitors (TNFis) on spinal radiographic progression in ankylosing spondylitis (AS).MethodsPatients with AS in the Swiss Clinical Quality Management cohort with up to 10 years of follow-up and radiographic assessments every 2 years were included. Radiographs were scored by two readers according to the modified Stoke Ankylosing Spondylitis Spine Score (mSASSS) with known chronology. The relationship between TNFi use before a 2-year radiographic interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
237
4
13

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(265 citation statements)
references
References 34 publications
(36 reference statements)
11
237
4
13
Order By: Relevance
“…Anti‐TNF‐α and, more recently, anti‐IL‐17 antibodies are currently being used as a treatment to relieve pain for SpA patients in addition to nonsteroidal anti‐inflammatory drugs . Long‐term follow‐up studies have revealed that these biotherapies also slow radiographic progression of spinal fusion . In interaction with inflammation, mechanical stress is also assumed to participate in SpA pathogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…Anti‐TNF‐α and, more recently, anti‐IL‐17 antibodies are currently being used as a treatment to relieve pain for SpA patients in addition to nonsteroidal anti‐inflammatory drugs . Long‐term follow‐up studies have revealed that these biotherapies also slow radiographic progression of spinal fusion . In interaction with inflammation, mechanical stress is also assumed to participate in SpA pathogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…Extensions of pivotal randomized clinical trials (RCTs) failed to show an inhibitory effect of adalimumab, infliximab, and entanercept on spinal structural changes over a period of 2 years . However, accumulating evidence from retrospective analyses of well‐characterized cohorts shows that TNF inhibitors are associated with a reduction in spinal radiographic progression, an effect attributed to their ability to suppress disease activity . The need for an extended prospective RCT against placebo that could prove causality cannot be overstated; however, such studies would be impossible to conduct due to ethical considerations.…”
Section: Tnf Inhibitors In Treatment Of Asmentioning
confidence: 99%
“…Currently there are five anti‐TNF agents available for clinical use in ankylosing spondylitis: adalimumab (ADA) and golimumab (both fully human monoclonal antibodies), infliximab (IFX; chimeric monoclonal antibody with a murine variable region), certolizumab (humanized Fab fragment conjugated to polyethylene glycol), and etanercept (ETN; fusion protein of 2 TNFR2 receptor extracellular domains and the Fc fragment of human immunoglobulin 1). TNF inhibitors proved to be effective in patients with ankylosing spondylitis in improving clinical symptoms, and in long‐term use they may prevent structural damage progression . TNF inhibitors are indicated in patients with ankylosing spondylitis with failure of standard treatment and high disease activity (Ankylosing Spondylitis Disease Activity Score ≥2.1 or Bath Ankylosing Spondylitis Disease Activity Index ≥4) .…”
mentioning
confidence: 99%